The position of the Russian ruling systems towards Muslims in Russia: the international and political journal - Ismail , Batool Tariq; Alwan, Batuol Hussain (The International and Political Journal, 2025)
Religion plays a prominent role in directing the policy of countries at the internal and external levels, as religion helps at the internal level to achieve social stability, especially if countries guarantee in their constitutions freedom of belief and practice, and translate this on the ground, and with regard to Russia, religion was one of the factors on which it relied in its position To words its citizens who do not believe in the religion of the ruling authority (Muslims), as dealing with them varied according to the orientations of the political authority, they were persecuted in periods of the rule of the Tsars as well as the case during the rule of the Marxists (Soviet Union), but after the collapse of the Soviet Union, Russia emphasized the importance of diversity within its territory and considered it a factor of strength rather than weakness employed in its policies and relations with other countries.